Analysis of The Negative Economic Impact of Online Gambling: A Case Study in The Sub-District of Bojong - Regina Silfiana; Hendri Hermawan Adinugraha; Hanif Zaidaan Hakim (Journal of Noesantara Islamic Studies, 2024)
This study aims to determine the negative economic impacts associated with the rise of online gambling. The method used in this research is descriptive qualitative. The theory used in this research is the Differential Association Theory by Edwind H. Sutherland. This research concludes that in Bojong Sub-district, many people play online gambling. The triggering factors vary, including easy access to the internet, the unemployment rate, socialization, and the many online gambling promotions on social media. The negative economic impact is enormous, such as financial losses, changes in spending priorities, and decreased productivity. Teenagers tend to be more susceptible to online gambling than adults because teenagers are more technologically literate. People with lower social status have a higher risk of financial loss than people with high social status. Based on the research findings, there needs to be a strategy for the Bojong Sub-district government to deal with this online gambling problem